Method for regenerating zeolite-based hydrocracking catalyst and use thereof in hydrocracking process

By heating and/or hydrothermal treatment of the failed hydrocracking catalyst in the presence of oxygen-containing gas at a temperature of 350°C to 460°C, the problem of insufficient catalyst activity and yield is solved, and the catalyst performance is significantly improved and the process flow is simplified.

CN119604361APending Publication Date: 2025-03-11IFP ENERGIES NOUVELLES
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380055405.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-22
Filing Date
2023-07-04
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regenerate and restore bifunctional hydrocracking catalysts, resulting in insufficient catalyst activity and yield, affecting product quality.

Method used

The regeneration method is adopted to heat and/or hydrothermal treatment of at least partially failed catalysts in the presence of oxygen-containing gas at a temperature of 350°C to 460°C, and the regeneration catalyst is directly obtained.

Benefits of technology

The regeneration catalyst obtained by this method exhibits similar or higher conversion activity and hydrogenation properties to the fresh catalyst in the hydrocracking reaction without the need for a restoration treatment, reducing energy consumption and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604361A_ABST
    Figure CN119604361A_ABST
Patent Text Reader

Abstract

The present invention relates to a process for regenerating an at least partially deactivated catalyst resulting from a hydrocracking process, said at least partially deactivated catalyst originating from a fresh catalyst comprising at least one metal of Group VIII, at least one metal of Group VIB and a support comprising at least one zeolite, the process comprises at least one regeneration stage in which the at least partially deactivated catalyst is subjected to heating and / or hydrothermal treatment in the presence of an oxygen-containing gas at a temperature of 350 DEG C to 460 DEG C to obtain a regenerated catalyst, the process does not include a subsequent recovery stage of contacting the regenerated catalyst with at least one organic or inorganic and acidic or basic compound.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for regenerating a hydrocracking catalyst without a chemical modification stage, and to the use of the regenerated catalyst in the field of hydrocracking. The present invention also relates to a regenerated catalyst obtained by the regeneration method according to the invention. Prior art

[0002] The hydrocracking of heavy petroleum fractions is a key process in oil refining, which makes it possible to prepare light fractions, such as petroleum, jet fuel and light gas oil, from the remaining and not easily upgradable heavy feedstocks, and oil refineries are looking for these light fractions to adjust their production according to demand. For example, some hydrocracking processes also make it possible to obtain highly purified residues, which can constitute an excellent base material for oil or a feed material that is easy to upgrade in a catalytic cracking unit. One of the effluents that the hydrocracking process is particularly directed to is the middle distillate (a fraction containing gas oil fractions and kerosene fractions), but depending on whether the catalytic reforming or steam cracking unit is integrated into the complex, the prepared gasoline can also be upgraded, especially for the feed route for the preparation of petrochemical intermediates. Another advantage of hydrocracking is that the use of a strong hydrogenating function makes it possible to obtain an effluent, the quality of which is very attractive as a fuel base material. Particular mention will be made of the cetane number of the gas oil obtained, which is the best on the market, in particular because of the preparation conditions under which the process is carried out and which result in a high degree of hydrogenation of the aromatic compounds. Mention may also be made of the viscosity index of the unconverted oil, which will be of particular benefit to engine manufacturers.

[0003] Hydrocracking catalysts are usually classified based on the nature of their acid function, in particular catalysts comprising amorphous acid functions of the silica-alumina type and catalysts comprising zeolitic cracking functions, such as zeolite Y or zeolite beta, indeed even mixtures of several zeolites.

[0004] Hydrocracking catalysts are also classified according to the main products obtained during their use in the hydrocracking process, the two main products being middle distillates and naphtha. The term "naphtha fraction" or "naphtha" is understood to refer to a petroleum fraction having a boiling point lower than that of the middle distillate fraction. In order to maximize the yield of kerosene and gas oil, the middle distillate fraction generally has a cut point of 150°C to 370°C. However, for example in a process specifically related to the preparation of naphtha, in order to increase the yield of naphtha, the lower cut point of the middle distillate fraction can be increased. For this purpose, the naphtha fraction can have a boiling point of a hydrocarbon compound having 6 carbon atoms in each molecule (or a boiling point of 68°C) to a boiling point of up to 216°C, and includes a gasoline fraction. Similarly, the cut point of the middle distillate can be varied to increase the yield as long as the product remains within the effective specification (which itself depends on the geographical area of ​​use).

[0005] It is known to use catalysts based on FAU type zeolites to prepare the light fractions, gasoline or middle distillates, which are more upgradable. These acidic solids are most often used for molding in an aluminum matrix used as a binder. Then, after impregnation and activation of the metal phase on the aforementioned molding support, a bifunctional type catalyst is obtained. Generally, it is generally believed that these catalysts are composed of a metal from Group VIB selected from molybdenum or tungsten and a metal from Group VIII selected from cobalt or nickel.

[0006] Catalysts of this type are not usually recycled by the refinery in a short loop, the catalyst then being discharged for separate recycling of the various components of the latter, among which in particular the metals recovered by the metallurgical industry. However, in some cases it may be advantageous to reprocess the catalyst in one or more stages in order to insert the catalyst into a new catalytic cycle of a hydrocracking unit. The current prior art for achieving this includes the following examples.

[0007] Patent US9266099 (Cosmo Oil) describes a method for the regeneration of a hydrocracking catalyst consisting of a zeolite providing acid functionality and a metal phase selected from groups VIB and VIII and carrying hydrogenation functionality. The spent catalyst obtained by the above method generally contains between 0.05% and 1% by weight of carbon, preferably consisting of platinum and USY type zeolite, which is used for the hydrocracking of Fischer-Tropsch waxes. The regeneration method is based on a preliminary stage of washing the carbon-based raw material residues present in the pores before burning the coke in an oxidizing atmosphere at an intermediate temperature of 250°C to 400°C, before a stabilization stage at a second higher temperature of 350°C to 550°C. The examples of this patent teach us that if the aim is to maintain high activity and high selectivity in hydrocracking, it is preferred to regenerate at higher temperatures, i.e. 450°C (according to the embodiments of the invention) instead of 430°C (comparative example).

[0008] Patent FR2771950 (IFPEN) describes a method for the regeneration of acidic solids comprising at least one refractory oxide and / or at least one molecular sieve, which have been used to treat hydrocarbon feedstocks. To this end, the spent solids are treated at a temperature ranging from 320°C to 550°C in the presence of a nitrogen oxide precursor chosen from nitrate or nitrite anions, nitroxyl, nitrosyl or NH4 + Cations, or organic compounds containing nitro, nitroso, amino or ammonium functional groups.

[0009] Patent FR2498477 (IFPEN) describes a method for the regeneration of acidic solids, also composed of at least one metal selected from groups IB, IIB or VIII. For this purpose, the spent solids are treated at a temperature ranging from 300°C to 600°C before being treated at a lower temperature of less than 200°C in the presence of 0.5% to 100% steam.

[0010] Generally, however, in the case of “bifunctional” hydrocracking solids, the above-mentioned regeneration methods do not make it possible to restore the performance qualities of the catalysts, and their applicability therefore remains small for industrialists, who prefer fresh catalysts.

[0011] In the case of hydroprocessing catalysts, solutions to overcome this problem have been found. Thus, the addition of organic compounds, that is to say without acid functionality, in particular zeolites or silica-aluminas, to hydroprocessing catalysts is well exemplified in the literature. Their introduction makes it possible to improve the activity of catalysts prepared by impregnation followed by drying but without subsequent calcination. These catalysts are generally referred to as "dry catalysts impregnated with additives".

[0012] In order to overcome the lack of hydrodesulfurization activity of the regenerated catalyst, the skilled person may therefore rely on an additional "rejuvenation" treatment. The restoration method comprises re-impregnating the regenerated catalyst with a solution containing a metal precursor in the presence or absence of an organic or inorganic additive. These "rejuvenation" methods are well known to those skilled in the art in the field of middle distillates. Many patents, such as, for example, US7906447, US 8722558, US7956000, US7820579, FR2972648, US2017 / 036202 or CN102463127, therefore provide different methods for implementing the restoration of the catalyst used for the hydrotreatment of middle distillates.

[0013] Document US7956000 describes in particular a rejuvenation process in which a catalyst comprising an oxide of a metal from group VIB and an oxide of a metal from group VIII is contacted with an acid and an organic additive having a boiling point of 80°C to 500°C and a solubility in water of at least 5 g / l (20°C, atmospheric pressure), optionally followed by a drying operation under conditions such that at least 50% of the additive remains in the catalyst. The hydroprocessing catalyst may be a fresh hydroprocessing catalyst or a spent hydroprocessing catalyst that has been regenerated.

[0014] Document US2014076780 describes a method for obtaining a catalyst comprising an amorphous support based on aluminum oxide, di(C1-C4) alkyl succinate, citric acid and optionally acetic acid, phosphorus, and a hydrodehydrogenation functional group comprising at least one element from group VIII and at least one element from group VIB. The method for preparing the catalyst comprises impregnating a catalytic precursor (which may be in a dry, calcined or regenerated state) with an impregnation solution comprising at least di(C1-C4) alkyl succinate and citric acid. The document teaches us that this restoration treatment makes it possible to particularly remove the anti-sulfurization crystalline phase generated during high temperature heat treatment.

[0015] There are far fewer documents describing methods for the rejuvenation of hydrotreating catalysts as proposed above, no doubt because of the complexity of implementation, since on a bifunctional catalyst both the hydrogenation function and the acid function must be restored simultaneously. However, some documents are reproduced below.

[0016] Patent US5206194 (Union Oil Company) describes a method for rejuvenating a hydrocracking catalyst consisting of an acid function selected from a wide list of zeolites including USY CBV720, CBV712 or LZ-210 and a hydrogenation function provided by a metal from group VIII selected from platinum or palladium. The spent catalyst consists of 2% to 20% of carbon and is regenerated before reactivation. The catalyst regenerated at 510° C. to 680° C. contains less than 1% by weight of carbon and is rejuvenated with a solution consisting of an ammonium salt, preferably selected from ammonium nitrate, ammonium carbonate or ammonium bicarbonate. The hydrocracking catalyst obtained is used under conditions such that the equivalent nitrogen content is less than 200 ppm. The examples of this document teach us very clearly that, whether it concerns the first hydrocracking stage or the second stage, a relatively high optimum regeneration temperature is necessary, which is between 540° C. and 590° C. (respectively between 1000° F. and 1100° F.) in order to maximize the conversion activity, but in both cases this temperature does not make it possible to achieve an activity comparable to that of the fresh catalyst. The rejuvenation stage makes it possible to improve the performance qualities, but, like the individual regenerations, these teachings lead us to aim at high regeneration temperatures.

[0017] Patent application US20130137913 (Shell) describes a method for restoring a zeolite catalyst, which is preferably used for converting oxygen-based compounds into olefins of at least four carbon atoms. The acid function of the catalyst is provided by 10-MR zeolite. The restoration treatment includes treating the catalyst with an acid solution consisting of acetic acid, oxalic acid or tartaric acid, or with an acidified ammonia solution consisting of various inorganic or organic acids selected from HCl, HBr, HI, nitric acid, sulfuric acid or p-toluenesulfonic acid. In addition, the failed catalyst can be pre-heat-treated in an oxidizing medium with O2, O3, SO3, N2O, NO, NO2 or N2O5 at a temperature of 550°C to 750°C as required, but the treatment can also be carried out before the stage of restoration with an organic acid. The examples in this document teach us that a single regeneration leads to a very sharp drop in activity, and restoration improves performance quality, but makes it impossible to achieve a conversion rate comparable to that of a fresh catalyst.

[0018] Patent application US2018318822 (ExxonMobil) describes a method for regeneration and restoration of a spent catalyst. The spent catalyst is essentially bifunctional, having a zeolite or a mixture of several zeolites and a metal phase consisting of a metal from group VIB and a metal from group VIII. The patent application is directed to use in catalytic dewaxing. The spent catalyst is first regenerated under air at a temperature of 370°C to 710°C to remove coke and obtain a calcined catalyst, which is then contacted with a solution containing a complexing agent, wherein the molar ratio of the complexing agent to the metal is 1.25 to 10. Finally, the catalyst thus restored is dried only at low temperature. Citric acid is preferred, and ethylene glycol can also be used as a complexing agent, and optionally both can be impregnated as a mixture. Again, regardless of the functionality of the catalysts shown in the examples, the improvements in HDS, HDN, cloud point (which is related to the isomerization activity of the catalyst), the performance quality of the regenerated catalyst at 540°C was lower than that of the fresh catalyst, and regeneration brought improvements, but was still not enough to restore the performance quality of the fresh catalyst.

[0019] Therefore, it seems that there is no sufficiently attractive technical solution to make the regeneration or recovery of a bifunctional hydrocracking catalyst consisting of a metal phase based on a metal from Group VIB and from Group VIII and an acid phase consisting of at least one zeolite. Examples in the literature generally report insufficient catalytic activity or yield. In addition, no information is provided about the hydrogenation performance quality of the regenerated catalyst to be obtained, but based on the teachings established in the field of hydroprocessing catalysts, it seems obvious that if the hydrocracking catalyst is not recovered after a separate regeneration stage, a significant degradation of product quality (such as the cetane number of gas oil) must be endured.

[0020] The object of the present invention is therefore to provide a regeneration process which brings about at least maintaining, indeed even improving, the conversion activity and / or the hydrogenation properties of a hydrocracking catalyst based on metals of group VIII and from group VIB and zeolites, relative to the corresponding fresh catalyst, said catalyst having previously been deactivated during a working cycle of the hydrocracking reaction. In particular, the present invention relates to the treatment of spent catalysts in a hydrocracking process of hydrocarbon feedstocks of any origin (fossil and / or vegetable and / or animal and / or obtained from plastics), these hydrocarbon feedstocks having at least 2% by weight of coke relative to the fresh catalyst, at a target conversion level predetermined by the refinery (and generally ranging from 60% to 90% of the conversion of the hydrocarbon feedstock to be treated) and having undergone an activity loss of at least 7°C.

[0021] This is because the Applicant Company has surprisingly found that, contrary to the repeated teachings of the prior art, carrying out the process for regenerating a spent hydrocracking catalyst comprising at least one metal from group VIII, at least one metal from group VIB and at least one acid function at a sufficiently low temperature, i.e. below 460° C., makes it possible to obtain a hydrocracking catalyst having improved catalytic performance qualities compared to a catalyst regenerated at a higher temperature, in this case without resorting to a rejuvenation treatment. SUMMARY OF THE INVENTION

[0023] The present invention relates to a process for regenerating an at least partially spent catalyst resulting from a hydrocracking process, the at least partially spent catalyst resulting from a fresh catalyst comprising at least one metal from group VIII, at least one metal from group VIB and a support comprising at least one zeolite, the process comprising at least one regeneration stage in which the at least partially spent catalyst is subjected to a heating and / or hydrothermal treatment at a temperature ranging from 350° C. to 460° C. in the presence of an oxygen-containing gas, so as to obtain a regenerated catalyst, the process not comprising a subsequent regeneration stage in which the regenerated catalyst is contacted with at least one organic or inorganic and acidic or basic compound.

[0024] An advantage of the present invention is that it provides a regeneration process operating at low temperatures, which makes it possible to obtain a regenerated hydrocracking catalyst having improved catalytic performance qualities compared to prior art catalysts regenerated at higher temperatures, and in this case without resorting to a rejuvenation treatment.

[0025] Another advantage of the present invention is to provide a method for regenerating a hydrocracking catalyst which makes it possible to maintain at least the conversion activity and / or the hydrogenation properties of said catalyst relative to the corresponding fresh catalyst.

[0026] The term "maintaining activity" is understood here to mean that the temperature difference applied in order to obtain the target conversion of the hydrocarbon feedstock (generally vacuum distillate) is minimal, in practice even zero, compared to a fresh catalyst and is at a maximum compared to a spent catalyst. The term "maintaining the HDN and HOA performance qualities and indirectly maintaining the cetane number" is also understood to mean the fact that a regenerated catalyst can be obtained having performance qualities as close as possible to those of a fresh catalyst and therefore the best possible compared to a spent catalyst.

[0027] Without being bound to any theory, it seems that, unlike hydrotreating catalysts consisting solely of amorphous oxides without zeolitic acid functions in their support, hydrocracking catalysts form relatively little sulfidation-resistant crystalline phases, such as NiMoO4, at low regeneration temperatures, which makes it possible to avoid resorting to additional treatment stages by rejuvenation with compounds, whatever their nature, thereby simplifying the post-processing of the spent catalyst.

[0028] Therefore, another advantage of the present invention is to provide a regeneration process that is economically attractive to industrialists and environmentally sustainable.This result appears to be specific to hydrocracking catalysts prepared based on non-precious metals such as nickel, cobalt, molybdenum or tungsten.

[0029] The invention also relates to the use of the regenerated catalyst prepared according to the process of the invention in a process for the hydrocracking of hydrocarbon fractions.

[0030] The invention also relates to a regenerated catalyst obtained by the regeneration method according to the invention.

[0031] Characterization techniques

[0032] Subsequently, the groups of chemical elements are given according to the CAS classification (CRC Handbook of Chemistry and Physics, published by CRC Press, edited by DRL De, 81st edition, 2000-2001). For example, group VIII according to the CAS classification corresponds to metals in columns 8, 9 and 10 according to the new IUPAC classification.

[0033] The various atomic contents in the zeolite, alumina precursor, support or catalyst are measured by X-ray fluorescence, by atomic absorption spectroscopy, by inductively coupled plasma (ICP) spectroscopy or by combustion using the method most appropriate for the values ​​measured.

[0034] The content of metals from group VIB, metals from group VIII and optionally phosphorus in a fresh catalyst, in an at least partially spent catalyst or in a regenerated catalyst, expressed as oxides after correction for the loss on ignition of the catalyst samples. This correction makes it possible to compare the metal contents of fresh, at least partially spent and regenerated catalysts. The loss on ignition of a catalyst corresponds to the sum of its content of water, carbon, sulphur, nitrogen and / or any other contaminants which are removed by the heat treatment used to measure this loss on ignition. The latter (loss on ignition) is measured after a heat treatment at 550° C. for 1.5 hours in a muffle furnace.

[0035] Unlike the metal content, the carbon or sulphur content in an at least partially spent catalyst or in a regenerated catalyst is expressed relative to the total weight of the catalyst under consideration without correction for loss on ignition.

[0036] The lattice constant a0 or lattice parameter of the zeolite unit cell is measured by X-ray diffraction (XRD) according to standard ASTM 03942-80. X-ray diffraction is carried out using a PANalytical X'Pert Pro diffractometer operating in reflection and equipped with a post-monochromator using CuKα radiation.

[0037] According to the ICDD database, PDF table 00-012-0348, the NiMoO4 crystal phase has several diffraction lines, the most intense line is located at The lattice spacing d and the angular position q are related by Bragg's law (where n is the diffraction order = 1, and l is the wavelength of the X-ray ):2dsin(q)=nl

[0038] In this specification, the term "specific surface" or "BET surface area" of a zeolite, a support or a catalyst is understood to mean the BET specific surface determined by nitrogen adsorption according to standard ASTM D3663-78, which standard is drawn up by the Brunauer-Emmett-Teller method described in the journal "The Journal of the American Chemical Society", 60, 309 (1938). Four pressure points are used, p / p0=0.050, 0.075, 0.100 and 0.125. Before measuring the nitrogen adsorption-desorption isotherm, the sample is placed in a high vacuum (10 -4 The pretreatment was carried out at 450°C for 4 hours.

[0039] The pore distribution measured by nitrogen adsorption is determined by the Barrett-Joyner-Halenda (BJH) model. The nitrogen adsorption-desorption isotherm according to the BJH model is described in The Journal of the American Chemical Society", 73, 373 (1951) by EP Barrett, LG Joyner and PP Halenda. The term "total pore volume" of a zeolite, a carrier or a catalyst is understood to mean the volume measured by nitrogen adsorption at p / p0 = 0.99, at which pressure it is considered that nitrogen has filled all pores.

[0040] The term "mesopore volume" of a zeolite is understood to mean the difference between the total pore volume and the micropore volume described above. The micropore volume is also determined from the nitrogen adsorption-desorption isotherm using the "t" method (Lippens-De-Bor method, 1965), which corresponds to the transformation of the nitrogen adsorption isotherm, as described in the book "Adsorption by Powders and Porous Solids. Principles, Methodology and Applications", by F. Rouquérol, J. Rouquèrol and K. Sing, Academic Press, 1999. Eight pressure points are used, p / p0=0.075, 0.100, 0.125, 0.150, 0.175, 0.200, 0.250 and 0.300.

[0041] In the continuation of this document, the expressions "from ... to ..." and "... to ..." are equivalent and mean that the limits of the interval are included in the described value range. If this is not the case, and if the limits are not included in the described range, the present invention will introduce such clarification.

[0042] Within the meaning of the present invention, various parameter ranges (such as pressure ranges and temperature ranges) for a given stage can be used alone or in combination. For example, within the meaning of the present invention, a preferred range of pressure values ​​can be combined with a more preferred range of temperature values.

[0043] The term "hydroprocessing" is understood to mean reactions which include in particular hydrodesulfurization (HDS), hydrodenitrogenation (HDN) and hydrogenation of aromatics (HOA).

[0044] In contrast, hydrocracking includes all reactions that involve lowering the boiling point of the compounds present in the feedstock. In other words, it is mentioned that compounds with a boiling point greater than the target temperature are converted into products with a boiling point lower than this same temperature. The choice of temperature depends on the process and the feedstock. For processes aimed at maximizing gasoline, it is usually mentioned that the conversion is relative to a temperature in the vicinity of 150°C to 200°C, whereas for processes aimed at maximizing middle distillates (gas oils and kerosenes), the conversion will be determined at a temperature relative to about 350°C to 385°C.

[0045] The term "fraction X+" is understood to mean the combined compounds having a boiling point greater than the temperature X. The expression "net conversion of fraction X+" is understood to mean the difference between the yield of the fractions (or fractions) having a boiling point below the temperature X and the yield of the fractions having a boiling point below the temperature X present in the test feed, relative to the yield of the fractions having a boiling point greater than the temperature X in the feed, all the above yields being by weight.

[0046] Description of the invention

[0047] According to the invention, the present invention relates to a process for regenerating an at least partially spent catalyst resulting from a hydrocracking process, said at least partially spent catalyst resulting from a fresh catalyst comprising at least one metal from group VIII, at least one metal from group VIB and a support comprising at least one zeolite, said process comprising at least one regeneration stage in which the at least partially spent catalyst is subjected to a heating and / or hydrothermal treatment at a temperature ranging from 350° C. to 460° C. in the presence of an oxygen-containing gas, so as to obtain a regenerated catalyst, said process not comprising an additional regeneration stage of contacting the regenerated catalyst with at least one organic or inorganic and acidic or basic compound.

[0048] The regenerated catalyst obtained by the process according to the invention is produced from an at least partially spent catalyst, which itself is produced from a fresh catalyst, which has been used for a period of time in a process for the hydrocracking of hydrocarbon fractions and exhibits a significantly lower activity than the fresh catalyst, necessitating its replacement.

[0049] The term "at least partly spent catalyst" is understood to mean a catalyst which has been discharged from a hydrocracking process carried out under the conditions described below and which has not undergone a thermal treatment (also often called a regeneration phase) at a temperature greater than 250° C. in an air or oxygen-containing gas. It may have undergone a deoiling or washing phase.

[0050] Preferably, the term "at least partially spent catalyst" is understood to mean a catalyst used in a process for the hydrocracking of vacuum distillates having at least 2% by weight of coke and which, at a target conversion level predetermined by the refinery (and generally ranging from 60% to 90% conversion of the hydrocarbon feedstock to be treated), suffers an activity loss of at least 7°C, preferably from 7°C to 60°C and more preferably still from 10°C to 40°C relative to the fresh catalyst.

[0051] Target performance quality

[0052] The performance qualities of the regenerated hydrocracking catalyst obtained according to the invention can be compared according to the conversion activity relative to a determined cut point. For example, at a given temperature and under given operating conditions, the fraction of hydrocarbon feedstock with a boiling point greater than a given temperature (370°C for the "maximum middle distillate" process or 175°C for the "maximum naphtha" process, which is converted) can be evaluated. Another way to evaluate the catalyst is to look at the yield of the hydrocarbon fraction of interest under given conditions or for a given conversion, the latter being defined as above. Depending on the cut point that the refinery will expect, the fraction that seeks to maximize the yield can be just like heavy gasoline, kerosene or gas oil. Finally, the last criterion for evaluating the catalyst regenerated according to the method of the invention is its ability to hydrodenitrogenate hydrocarbon fractions, i.e. the percentage of organic nitrogen removal, or its ability to hydrogenate aromatic compounds, or its ability to obtain gasoline, kerosene, gas oil or unconverted oil fractions of favorable quality, which may be what the refinery seeks to maximize in its operation. As examples, mention will be made of the cetane number of a gas oil or the viscosity index of an unconverted oil, but by applying the method forming the subject of the present invention, other properties of the product can also be recovered.

[0053] Fresh Catalyst

[0054] Fresh catalysts for use in processes for hydrocracking of hydrocarbon fractions are known to those skilled in the art. They comprise at least one metal from group VIII, at least one metal from group VIB and a support comprising at least one zeolite as described below.

[0055] The metal from group VIB present in the active phase of the fresh catalyst is preferably selected from molybdenum and tungsten. The metal from group VIII present in the active phase of the fresh catalyst is preferably selected from cobalt, nickel and a mixture of these two elements. The active phase of the fresh catalyst is preferably selected from the combination of the elements nickel-molybdenum, cobalt-molybdenum, nickel-tungsten, nickel-molybdenum-tungsten and nickel-cobalt-molybdenum, and very preferably the active phase consists of nickel and molybdenum, nickel and tungsten or nickel-molybdenum-tungsten combinations.

[0056] The content of metal from group VIII in the fresh catalyst is less than 20% by weight, preferably from 0.03% to 15% by weight, very preferably from 0.5% to 10% by weight and still more preferably from 1% to 8% by weight, expressed as oxide of the metal from group VIII, relative to the total weight of the fresh catalyst.

[0057] The content of metal from Group VIB in the fresh catalyst is from 1 to 50% by weight, preferably from 5 to 40% by weight and more preferably from 10 to 35% by weight, expressed as oxide of the metal from Group VIB, relative to the total weight of the fresh catalyst.

[0058] The molar ratio of metal from group VIII to metal from group VIB of the fresh catalyst is generally less than 1, preferably from 0.01 to 0.75 and very preferably from 0.10 to 0.60.

[0059] Optionally, the fresh catalyst can additionally have a phosphorus content of P2O5 of typically less than 15% by weight, preferably from 0.1% to 10% by weight, very preferably from 0.1% to 8% by weight and still more preferably from 0.2% to 6% by weight, relative to the total weight of the fresh catalyst.

[0060] Furthermore, in the case where the fresh catalyst comprises phosphorus, the phosphorus / (metal from Group VIB) molar ratio is generally from 0.02 to 1, preferably from 0.04 to 0.8 and very preferably from 0.1 to 0.75.

[0061] According to the present invention, the support comprises at least one zeolite. The zeolite is preferably selected from zeolites belonging to the groups of FAU (including zeolite X, Y, USY and any other name of zeolite Y which has undergone dealumination), BEA, ISV, IWR, IWW, MEI, UWY, MEL, MTW, MTT, MRE, FER or MFI, and preferably, the zeolite is selected from 10-MR or 12-MR zeolites, or preferably from the groups of FAU or BEA. Some examples of zeolites resulting from the aforementioned families are mentioned below, without limiting the list of possible choices: ZSM-5 (MFI), ZSM-11 (MEL), ZSM-12 (MTW), ZSM-23 (MTT), ZSM-M35 (FER), ZSM-48 (MRE), CP841E, CP814C, CP811C-300, HSZB25, HSZB30, HSZB150, HSZ931, HSZ940, HSZ980 (BEA) or Y82, Y84, CP300-56, CBV712, CBV720, CBV760, CBV780, CBV500, HSZ320, HSZ330, HSZ331, HSZ385, HSZ350, HSZ360, HSZ390, HSZ341 or HSZ371 (FAU or USY).

[0062] Preferably, the support comprises zeolite USY and / or zeolite beta, alone or as a mixture, and preferably it comprises and preferably consists of zeolite USY.All methods for preparing zeolites can be applied in the preparation of zeolites for preparing fresh catalysts.

[0063] The content by weight of zeolite in the support is from 1% to 80% by weight, preferably from 2% to 70% by weight and very preferably from 3% to 60% by weight, relative to the total weight of the support.

[0064] When the support comprises a mixture of zeolite USY and zeolite β, the weight ratio of USY to β is 1 to 20, preferably 1.5 to 18, and still more preferably 2 to 15.

[0065] Preferably, when the support comprises zeolite USY, the latter has a lattice parameter of 24.10 to Preferably 24.15 to Still more preferably 24.20 to The Si / Al molar ratio is 2 to 300, preferably 2.5 to 150, still more preferably 2.5 to 100, and the BET specific surface is greater than 500 m 2 / g, preferably 600 to 1100m 2 / g, still more preferably 750 to 1000 m 2 / g, the mesopore volume is 0.05 to 0.9 ml / g, preferably 0.08 to 0.7 ml / g, and still more preferably 0.1 to 0.6 ml / g.

[0066] Preferably, when the support comprises zeolite beta, the latter has a Si / Al molar ratio of 5 to 300, preferably 6 to 200, still more preferably 6 to 100, a BET specific surface area of ​​greater than 500 m 2 / g, preferably 550 to 900m 2 / g, still more preferably 550 to 800 m 2 / g, the mesopore volume is 0.05 to 0.9 ml / g, preferably 0.1 to 0.9 ml / g, and still more preferably 0.15 to 0.85 ml / g.

[0067] The support may also advantageously comprise at least one oxide binder and is preferably a porous solid selected from alumina, silica, silica-alumina or titanium, boron, zirconium or magnesium oxides, used alone or in a mixture with alumina or silica-alumina. Preferably, the binder is based on alumina or silica or silica-alumina.

[0068] When the oxide binder is based on alumina, it contains more than 50% by weight of alumina relative to the total weight of the support and generally contains only alumina or silica-alumina as described below.

[0069] Preferably, the oxide binder comprises alumina. The alumina can advantageously be provided in all its forms known to the person skilled in the art. Preferably, the alumina is selected from alpha, rho, chi, kappa, eta and gamma alumina. Very preferably, the alumina is gamma alumina.

[0070] In another embodiment, the oxide binder is silica-alumina containing at least 50% by weight of alumina relative to the total weight of the oxide binder. The silica content in the binder is less than 50% by weight, typically less than 45% by weight, preferably less than 40% by weight relative to the total weight of the support.

[0071] When the binder of the catalyst is based on silica, it contains more than 50% by weight of silica relative to the total weight of the binder, and generally it contains only silica.

[0072] Preferably, the support comprising at least one zeolite advantageously has a diameter of 0.15 to 1.2 cm 3 .g -1 、 Preferably 0.18 to 1.1 cm 3 .g -1 、 And very preferably 0.2 to 1.0 cm 3.g -1 of the total pore volume.

[0073] The BET specific surface of the support comprising at least one zeolite is advantageously greater than 150 m 2 .g -1 , preferably 150 to 900 m 2 .g -1 , very preferably 180 to 850 m 2 .g -1 , and still more preferably 200 to 800 m 2 .g -1 .

[0074] The support is advantageously provided in the form of beads, extrudates, pellets or irregular and non-spherical agglomerates, the specific shape of which may result from a crushing stage.

[0075] Fresh catalyst can also add the organic compound containing at least one oxygen and / or nitrogen and / or sulphur before sulfidation.Such additive is well known to those skilled in the art.Usually, organic compound is selected from the compound containing one or more chemical functional groups, and described chemical functional group is selected from carboxylic acid, alcohol, mercaptan, thioether, sulfone, sulfoxide, ether, aldehyde, ketone, ester, carbonate (salt), amine, nitrile, imide, oxime, urea and amide functional group or comprises the compound of furan ring or sugar.

[0076] The content of oxygen- and / or nitrogen- and / or sulfur-containing organic compounds on the fresh catalyst is 1 to 30 wt %, preferably 1.5 to 25 wt %, and more preferably 2 to 20 wt %, relative to the total weight of the fresh catalyst.

[0077] The preparation of the fresh catalyst is known to those skilled in the art and generally comprises a stage of impregnation of metals from group VIB and from group VIII and optionally phosphorus and / or an organic compound on a support comprising at least one zeolite, followed by a drying operation and then an optional calcination, which makes it possible to obtain the metals in the form of their oxides. Before using it in a process for the hydrocracking of hydrocarbon fractions, the fresh catalyst is generally sulphurized to obtain the metals in their sulphurized or partially sulphurized form as described below.

[0078] According to one alternative form of the invention, when an organic compound is present, the fresh catalyst is not calcined during its preparation, ie the impregnated catalytic precursor does not undergo a thermal treatment stage at a temperature greater than 200° C., under an inert atmosphere or an oxygen-containing atmosphere, with or without water.

[0079] According to another alternative form of the invention, the fresh catalyst has undergone a calcination stage during its preparation, i.e. the impregnated catalytic precursor has undergone a heat treatment stage, typically for 15 minutes to 10 hours, in an inert atmosphere or an oxygen-containing atmosphere, in the presence or absence of water, at a temperature ranging from 200° C. to 1000° C., preferably from 250° C. to 750° C.

[0080] Depleted catalyst

[0081] During the process of hydrocracking of hydrocarbon fractions, coke, sulphur and nitrogen arising from the feedstock and possibly other contaminants such as silicon, arsenic and metals form and / or deposit on the catalyst and transform the fresh catalyst into an at least partially spent catalyst.

[0082] The term "at least partly spent catalyst" is understood to mean a catalyst which has been discharged from a hydrocracking process carried out under the conditions described below and which has not been subjected to a thermal treatment in a gas containing air or oxygen at a temperature greater than 250° C. (also often called a regeneration phase). It may have passed a deoiling or washing phase.

[0083] Preferably, the term "at least partially spent catalyst" is understood to mean a catalyst used in a process for the hydrocracking of vacuum distillates having at least 2% by weight of coke and which, at a target conversion level predetermined by the refinery (and generally ranging from 60% to 90% conversion of the hydrocarbon feedstock to be treated), suffers a loss in activity of at least 7°C, preferably from 7°C to 60°C, still more preferably from 10°C to 40°C, relative to a fresh catalyst.

[0084] The at least partially spent catalyst consists of a support comprising at least one zeolite and a hydrogenation phase formed by at least one metal from group VIB, at least one metal from group VIII, and carbon, sulfur, nitrogen and possibly other contaminants such as arsenic and metals arising from the feedstock.

[0085] The content of metals from group VIB and from group VIII and optionally phosphorus in the at least partly spent catalyst is essentially the same as in the fresh catalyst from which it was produced.

[0086] The term "substantially the same" is understood to mean that each of the metal elements mentioned is present in the same proportions as in the initial fresh catalyst, within a relative error of 5%.

[0087] It should be noted that the term "coke" or "carbon" in the present patent application refers to a hydrocarbon-based substance which is deposited on the surface of at least part of the spent catalyst during the use of the catalyst, and which has a highly cyclized and condensed structure.

[0088] The at least partially spent catalyst contains carbon in particular in a content of generally more than 2% by weight, preferably from 2.5 to 40% by weight, very preferably from 3 to 30% by weight and still more preferably from 3.5 to 25% by weight, relative to the total weight of the at least partially spent catalyst.

[0089] regeneration

[0090] The method for regenerating an at least partially spent catalyst according to the invention comprises a stage of removing at least part of the coke, sulfur and nitrogen at a relatively low temperature. According to the invention, the at least partially spent catalyst is subjected to a heating and / or hydrothermal treatment in the presence of an oxygen-containing gas at a temperature of 350° C. to 460° C. to obtain a regenerated catalyst.

[0091] Even if this is feasible, the regeneration is preferably not carried out by keeping the loaded catalyst in the hydrocracking reactor (in situ regeneration). Therefore, it is preferred that the at least partially spent catalyst is removed from the reactor and treated in a regeneration device to be regenerated in said device (ex situ regeneration).

[0092] Preferably, the regeneration stage is preceded by a deoiling stage. The deoiling stage preferably comprises contacting at least part of the spent catalyst with an inert gas stream (i.e. substantially free of oxygen), preferably in a nitrogen atmosphere or the like, at a temperature of 200° C. to 400° C., preferably 250° C. to 350° C. The inert gas flow rate (in terms of flow rate / unit volume of catalyst) is 5 to 150 sl.l -1 .h -1 The deoiling stage has a duration preferably ranging from 3 to 7 hours. It can advantageously be carried out in a hydrocracking unit, but can also be carried out ex situ, as is appropriate for the regeneration stage.

[0093] In one embodiment, the deoiling stage can be carried out by light hydrocarbons, by steam treatment or any other type of process.

[0094] In a preferred embodiment, the deoiling stage is replaced by a stage of washing with a hydrocarbon feedstock lighter than that used in the hydrocracking process, for example gas oil or a solvent liquid at ambient temperature, preferably an aromatic compound such as toluene or xylene. The washing is carried out at a temperature below 250° C. and can be carried out continuously according to a transverse bed arrangement or under reflux.

[0095] The deoiling stage makes it possible to remove soluble hydrocarbons that could prove hazardous during the regeneration stage, since they present a risk of flammability in an oxidizing atmosphere.

[0096] According to the invention, the regeneration stage comprises a heating and / or hydrothermal treatment in the presence of an oxygen-containing gas according to any technique known to the person skilled in the art. Such treatment can be carried out, for example, in a transversely moving bed, in a swept bed or in a static atmosphere. For example, the furnace used can be a rotary furnace or a vertical furnace or a belt furnace comprising radially penetrating layers.

[0097] According to the invention, the regeneration of the at least partially spent catalyst is carried out at a temperature of 350° C. to 460° C., preferably 360° C. to 450° C., in a preferred manner at 370° C. to 430° C., and still more preferably 380° C. to 420° C. The duration of the regeneration is preferably greater than 1 hour, more preferably 1 to 100 hours, in a preferred manner at 1.5 to 25 hours, and particularly preferably 2 to 10 hours. The oxygen content of the gas is lower than the oxygen content of air (20% v / v), preferably it is 2% to 20% v / v, more preferably 5% to 20% v / v, and still more preferably the gas used is air alone.

[0098] The water content of the gas is advantageously between 0 and 1000 g of water per kg of dry air, preferably between 0 and 500 g of water per kg of dry air, in a preferred manner between 0 and 250 g of water per kg of dry air and still more preferably between 0 and 100 g of water per kg of dry gas.

[0099] Preferably, the regeneration stage is carried out in an oxygen-containing gas stream. The gas flow rate of the at least partially depleted catalyst is preferably 20 to 2000 S1.1 according to flow rate / unit volume. -1 .h -1 , more preferably 30 to 1000S1.1 -1 .h -1 , and particularly preferably 40 to 500 S1.1 -1 .h -1 .

[0100] In an alternative form of the regeneration method, one or more temperature stabilization phases are carried out at a temperature below the maximum temperature of the regeneration phase.

[0101] In a preferred alternative form, the oxygen content of the gas is gradually increased from a content of 2% to 10% v / v to a maximum content of less than or equal to 20% v / v during at least one regeneration stabilization phase carried out in a single step or by including a stabilization phase with an intermediate proportion of oxygen; preferably, the oxygen content is gradually increased during the last regeneration stabilization phase carried out at 350°C to 460°C.

[0102] In case the at least partially spent catalyst is subjected to a hydrothermal treatment, the latter may be carried out instead of or in combination with the steam-free thermal treatment.

[0103] According to the invention, the process does not comprise a subsequent regeneration phase of contacting the regenerated catalyst with at least one organic or inorganic and acidic or basic compound, preferably chosen from complexing and / or chelating and / or polar organic compounds.

[0104] The regenerated catalyst comprises a metal phase formed by at least one metal from group VIB and at least one metal from group VIII and a support comprising at least one zeolite. After regeneration, the hydrogenation functions of the metals from group VIB and from group VIII comprising the regenerated catalyst are in partially oxidized form. Advantageously, it contains less NiMoO4 (from the metals located in the lattice spacing) than if the catalyst had been regenerated at a higher temperature (i.e. at a temperature strictly greater than 460° C.). Preferably, the catalyst contains no or only trace amounts of a crystalline phase, such as NiMoO4.

[0105] The content of metals from Group VIB and from Group VIII and optionally phosphorus in the regenerated catalyst is substantially the same as that of the at least partially spent catalyst and substantially the same as that of the fresh catalyst (which produced the at least partially spent catalyst). For this purpose, the content is expressed relative to the weight of the catalyst corrected for the loss on ignition (as described in the "Characterization Techniques" section). Again, the term "substantially the same" is understood to mean that each of the mentioned metal elements is present in the same proportion as in the at least partially spent catalyst or in the fresh catalyst derived therefrom, with an error of about 5%.

[0106] The regenerated catalyst is characterized by a BET specific surface area of ​​more than 80%, preferably more than 85% and very preferably more than 90% of the corresponding fresh catalyst.

[0107] The total pore volume of the regenerated catalyst is generally greater than 80%, preferably greater than 85% and very preferably greater than 90% of that of the corresponding fresh catalyst.

[0108] The regenerated catalyst obtained in the regeneration stage contains residual carbon in an amount of less than 2% by weight, preferably less than 1.5% by weight, particularly preferably less than 1% by weight and very preferably from 0.01% by weight to 0.8% by weight, relative to the total weight of the regenerated catalyst. The regenerated catalyst may also be free of residual carbon.

[0109] The regenerated catalyst may contain residual sulfur in an amount of less than 3% by weight, preferably less than 2% by weight, in a preferred manner between 0.01% by weight and 1.5% by weight, and still more preferably between 0.1% by weight and 1.2% by weight, relative to the total weight of the regenerated catalyst. The regenerated catalyst may also be free of residual sulfur.

[0110] Optionally, the regenerated catalyst may also have low levels of contaminants resulting from treatment of the feedstock with the fresh catalyst that produced the regenerated catalyst, such as arsenic, mercury, and metals such as nickel, vanadium, iron, calcium, or sodium.

[0111] Preferably, the arsenic or mercury content is less than 2000 ppm by weight and very preferably less than 1000 ppm by weight relative to the total weight of the regenerated catalyst.

[0112] Preferably, the content of each metal that will not be present in the initial formulation of the fresh catalyst is less than 1% by weight, and very preferably less than 5000 ppm by weight, relative to the total weight of the regenerated catalyst.

[0113] A further subject of the present invention relates to the catalyst obtained by the regeneration process according to the invention.

[0114] Vulcanization (optional stage)

[0115] Before being used in a hydrocracking process, it is advantageous to convert the regenerated catalyst obtained according to the process of the invention into a sulphurized catalyst to obtain the metals in sulphurized or partially sulphurized form. This activation or sulphurization stage is carried out by methods well known to those skilled in the art and is advantageously carried out in the presence of hydrogen and hydrogen sulphide under a sulphur-reducing atmosphere.

[0116] The regenerated catalyst is advantageously non-original position or in-situ sulfurized.Sulfiding agent is H2S gas, elemental sulfur, CS2, mercaptan, sulfide and / or polysulfide, hydrocarbon fractions of sulfur-containing compounds with boiling point lower than 400 ℃ or any other sulfur-containing compounds for activating hydrocarbon feedstock to sulfurize the catalyst.The sulfur-containing compound is advantageously selected from alkyl disulfide, for example dimethyl disulfide (DMDS), alkyl sulfide, for example dimethyl sulfide, mercaptan, for example n-butyl mercaptan (or 1-butyl mercaptan), and polysulfide compounds of tertiary nonyl polysulfide type.The catalyst can also be sulfurized by sulfur contained in the feedstock to be desulfurized.Preferably, the catalyst is sulfurized in-situ in the presence of a sulfurizing agent and a hydrocarbon feedstock.Very preferably, the catalyst is sulfurized in-situ in the presence of a hydrocarbon feedstock added with dimethyl disulfide.

[0117] Hydrocracking process

[0118] Finally, another subject of the present invention is the use of the catalyst regenerated according to the process of the invention in a process for the hydrocracking of hydrocarbon fractions.

[0119] The hydrocracking process of hydrocarbon fractions can be carried out in one or more fixed-bed reactors in series, wherein the various hydrotreating and / or hydrocracking sections of its composition are recycled. These schemes are well known to oil refineries and can be adjusted according to the needs in terms of selectivity or in terms of activity and yield. The two-stage process of recycling to the second reactor, the one-stage process of no longer recycling, recycling to the hydrotreating reactor or recycling to the one-stage process of the hydrocracking reactor will be mentioned in particular. All alternative forms known to those skilled in the art can be applied to the purposes of the catalyst according to the present invention. In other words, if the oil refinery integrates other stages in the upstream or downstream of hydrocracking, such as, for example, hydrotreating, this is still in the field of purposes that can be envisioned according to the present invention.

[0120] The process of hydrocracking of hydrocarbon fractions is carried out in the presence of a catalyst regenerated according to the process of the invention in at least one of the reactors it constitutes. It can also be carried out in the presence of a mixture of regenerated catalyst and fresh catalyst or catalyst of any other source.

[0121] The metal phase, acid phase and support of the fresh catalyst may be the same or different from those present in the regenerated catalyst. In particular, where the performance quality of the regenerated catalyst is not identical to the performance quality shown by the corresponding fresh catalyst, the refinery may decide to string together one or more other fresh catalysts showing different catalytic performance qualities so that the sequence meets the method requirements. The catalytic performance quality thus regulated may be activity, yield or selectivity in the hydrocarbon product of interest, or the hydrogenation of HDN, aromatic compounds or the fine properties of the product, such as the cetane number of gas oil or the viscosity index of unconverted oil, and these target properties themselves do not constitute a restriction to the subject matter of the present invention.

[0122] In these hydrocracking processes, the operating conditions are those described below. They may vary, in the case where several hydrocracking reactors will constitute the process, according to implementation rules known to those skilled in the art.

[0123] Advantageously, the catalyst according to the invention is used in the hydrocracking process according to the invention after a "pretreatment" section containing one or more hydrotreating catalysts, which may be any catalyst known to those skilled in the art and which makes it possible to reduce the content of certain pollutants in the feedstock, such as nitrogen, sulfur or metals. The operating conditions of this "pretreatment" section (hourly space velocity, temperature, pressure, hydrogen flow, hydrocarbon flow, reaction configuration, etc.) may be diverse and vary according to the general knowledge of those skilled in the art.

[0124] raw material

[0125] A highly diverse range of feedstocks can be processed by the hydrocracking process according to the invention. The feedstock used in the hydrocracking process according to the invention is preferably a hydrocarbon feedstock in which at least 5% by weight of the compounds have an initial boiling point greater than 300° C. and a final boiling point less than 650° C., wherein preferably at least 30% by weight, in a preferred manner at least 50% by weight, and more preferably at least 75% by weight of the compounds have an initial boiling point greater than 300° C. and a final boiling point less than 650° C.

[0126] The feedstock is advantageously chosen from LCO (light cycle oil, light gas oil resulting from a catalytic cracking unit), atmospheric distillates, vacuum distillates, such as gas oils resulting, for example, from direct distillation of crude oil or from conversion units such as fluidized catalytic cracking (or fluidized catalytic cracking FCC), coking or visbreaking, feedstocks originating from units for extracting aromatics from lubricating oil base stocks or resulting from solvent dewaxing of lubricating oil base stocks, distillates from fixed-bed or ebullating-bed desulfurization or hydroconversion processes of ATR (atmospheric residue) and / or VR (vacuum residue) and / or deasphalted oils, and deasphalted oils, paraffins resulting from the Fischer-Tropsch process, alone or as a mixture. Mention may be made of feedstocks of renewable origin such as vegetable oils, animal fats, oils from the hydrothermal conversion or pyrolysis of lignocellulosic biomass, and plastic pyrolysis oils. The above enumeration is not limiting. The feedstock preferably has a T5 boiling point greater than 300°C, preferably greater than 340°C, ie 95% of the compounds present in the feedstock have a boiling point greater than 300°C, preferably greater than 340°C.

[0127] The nitrogen content of the feedstock treated in the process according to the invention is advantageously greater than or equal to 500 ppm by weight, preferably from 500 to 10000 ppm by weight, more preferably from 700 to 4000 ppm by weight and still more preferably from 1000 to 4000 ppm by weight. The sulfur content of the feedstock treated in the process according to the invention is advantageously from 0.01% to 5% by weight, preferably from 0.2% to 4% by weight and still more preferably from 0.5% to 3% by weight.

[0128] The feedstock may optionally contain metals. The cumulative content of nickel and vanadium in the feedstock treated in the process according to the invention is preferably less than 1 ppm by weight.

[0129] The feedstock may optionally contain asphaltenes. The asphaltenes content is typically less than 3000 ppm by weight, preferably less than 1000 ppm by weight, more preferably less than 200 ppm by weight.

[0130] Advantageously, when the catalyst obtained according to the process of the invention is used after the hydrotreatment section as described above, the content of nitrogen, sulfur, metals or asphaltenes in the liquid injected into the process according to the invention using the catalyst obtained according to the process of the invention is reduced. Preferably, the organic nitrogen content of the feedstock treated in the hydrocracking process according to the invention is from 0 to 200 ppm, preferably from 0 to 50 ppm and still more preferably from 0 to 30 ppm after hydrotreatment. The sulfur content is preferably less than 1000 ppm and the asphaltene content is preferably less than 200 ppm, while the content of metals (Ni or V) is less than 1 ppm.

[0131] The hydrocracking process according to the invention may comprise a fractionation stage between the pretreatment of the feedstock and the hydrocracking reactor using the catalyst according to the invention. In the preferred case where the hydrocracking process is carried out between the pretreatment and the hydrocracking reactor using the catalyst obtained according to the process according to the invention without fractionation (of gas and liquid), the nitrogen and sulfur removed from the liquid after the pretreatment are injected in the form of NH3 and H2S into the reactor containing the catalyst according to the invention.

[0132] Operating conditions of the hydrocracking process

[0133] Preferably, the hydrocracking process of the hydrocarbon feedstock is carried out at a temperature of 200° C. to 480° C., at a total pressure of 1 MPa to 25 MPa, with a volume ratio of hydrogen per volume of hydrocarbon feedstock of 80 to 5000 l / l, and at an hourly space velocity (HSV) of 0.1 to 50 h -1 In the implementation below, the hourly space velocity is defined by the ratio of the volume flow of hydrocarbon feedstock per volume of catalyst charged to the reactor.

[0134] Preferably, the hydrocracking process is carried out in the presence of hydrogen at a temperature of 250°C to 480°C, preferably 320°C to 450°C, very preferably 330°C to 435°C, at a pressure of 2 to 25 MPa, preferably 3 to 20 MPa, at a space velocity of 0.1 to 20 h / min. -1 , preferably 0.1 to 6h -1 , preferably in 0.2 to 3h -1 The process is carried out under the following conditions: the reaction mixture is heated to 40 ℃ and the amount of hydrogen introduced is such that the volume ratio of hydrogen per volume of the hydrocarbon feedstock is 100 to 2000 l / l.

[0135] The operating conditions used in the hydrocracking process according to the invention generally make it possible to achieve a single-pass conversion of greater than 15% by weight, and more preferably from 20% to 100% by weight, into products having a boiling point below 340°C, and preferably below 370°C.

[0136] The following examples illustrate the invention but do not limit its scope.

[0137] List of Figures

[0138] Figure 1 It shows that catalysts S1, R1 and R2 have a XRD diffraction patterns over a range of lattice spacing.

[0139] Figure 2 XRD diffractograms of catalysts S2, R3 and R4 in the same lattice spacing range are shown. For better readability, the diffractograms are offset relative to each other along the y-axis.

[0140] Located at the lattice spacing The diffraction line at is the strongest diffraction line of the NiMoO4 crystal phase. It does not exist on catalysts S1 and R2 ( Figure 1 ), nor on catalysts S2 and R4 ( Figure 2 ). On the other hand, it can be clearly seen on catalysts R1 and R3.

[0141] The other diffraction lines correspond to USY zeolite and internal standard (certified silica) added to the samples Example

[0142] Example 1: Obtaining the Expired Catalyst S1

[0143] Hydrocracking catalyst A was used for 2 years on a pilot hydrocracking unit operated as an industrial unit for vacuum distillates or VGO (vacuum gas oil). Catalyst A contained 16 wt. % MoO3, 3.5 wt. % NiO and 3.0 wt. % P2O5 deposited on a composite material consisting of 80 wt. % gamma alumina and 20 wt. % of alumina with a lattice parameter of Catalyst A has a zeolite content of 385 m 2 / g BET specific surface area and 0.60ml / g pore volume.

[0144] The hydrocracking unit in which catalyst A was implemented had a dual reactor design, the first reactor being intended for hydrotreating of the feedstock and the second reactor being intended for the hydrocracking itself. A NiMo / alumina type hydrotreating catalyst was loaded into the hydrotreating reactor. Catalyst A was loaded into the second reactor intended for hydrocracking. The feedstock used was of VGO type with an average T50 (by DS analysis) of around 430°C and a nitrogen content of 1400ppm.

[0145] Before the feedstock injection, both catalysts were sulfided using straight run gas oil (i.e. gas oil obtained from the direct distillation of oil) with the addition of 4 wt.% of dimethyl disulfide (DMDS) and 2 wt.% of aniline. -1(HSV=hourly space velocity), H2 / feedstock volume ratio of 1000 Sl / l, total pressure of 14 MPa and temperature of 350°C for 6 hours.

[0146] After sulphurization, the temperature of the first reactor is adjusted so as to achieve a target of 5 to 15 ppm of nitrogen at the outlet of this reactor throughout the cycle, and the temperature of the second reactor is adjusted so as to achieve a target of about 70% net conversion of the 370°C + fraction; in practice, this temperature varies from 376°C to 400°C. When the temperature of 400°C is no longer sufficient to maintain a conversion of 70%, the cycle is interrupted. On average, the catalyst thus undergoes a deactivation of 1°C / month.

[0147] After the catalyst was discharged from the hydrocracking reactor and subjected to an ex situ deoiling stage (washing with toluene at reflux at 250° C.), the catalyst was dried under low vacuum and then analyzed. The spent catalyst S1 was obtained; it contained 6% by weight of carbon.

[0148] Example 2: Obtaining regenerated catalyst R1 (comparison)

[0149] A portion of the spent catalyst S1 was subjected to a regeneration at 480° C. in an oxidizing atmosphere at a flow rate of 450 Sl / l / h of anhydrous air for 2 hours. A regenerated catalyst R1 was obtained which contained 0.25% by weight of sulfur and no longer contained carbon. Its metal composition was unchanged compared to the new catalyst A. XRD analysis showed the presence of a NiMoO4 phase which was not present on the spent catalyst S1, as shown in FIG. Figure 1 Catalyst R1 has 343m 2 / g, which accounts for 89% of the BET specific surface of the new catalyst A. It also has a pore volume of 0.57 ml / g, which accounts for 95% of the pore volume of the new catalyst A.

[0150] Example 3: Obtaining regenerated catalyst R2 (according to the present invention)

[0151] Another part of the spent catalyst S1 was subjected to regeneration at 400° C. in an oxidizing atmosphere at a water-free air flow rate of 450 Sl / l / h for 2 hours. A regenerated catalyst R2 was obtained, which contained 0.32% by weight of carbon and 1.1% by weight of sulfur. Its metal composition was unchanged compared to the new catalyst A. No NiMoO4 phase was detected by XRD analysis, as shown in FIG. Figure 1 shown.

[0152] Catalyst R2 has 362m 2 / g BET specific surface area and 0.57 ml / g pore volume, which account for 94% of the BET specific surface area and 95% of the pore volume of the new catalyst A, respectively.

[0153] Example 4: Obtaining the Spent Catalyst S2

[0154] Catalyst A described in Example 1 was also used in the same hydrocracking unit as in Example 1, but under temperature conditions that made it possible to achieve and maintain a net conversion of 85% in the 370°C+ fraction throughout the test. The initial temperature was set at 383°C and gradually increased over time to maintain the conversion level indicated. After 2.5 years, and while the temperature to be applied was 418°C, the unit was shut down and the hydrocracking catalyst was discharged. The latter thus experienced an average deactivation of about 1.2°C / month.

[0155] After a deoiling stage, as described in Example 1, the spent catalyst S2 was obtained; it contained 12% by weight of carbon.

[0156] Example 5: Obtaining regenerated catalyst R3 (comparison)

[0157] A portion of the spent catalyst S2 was regenerated at 480° C. in an oxidizing atmosphere at a water-free air flow rate of 450 Sl / l / h for 2 hours. A regenerated catalyst R3 was obtained which contained 0.14% by weight of sulfur and no longer contained carbon. Its metal composition was unchanged compared to the new catalyst A. XRD analysis showed the presence of a NiMoO4 phase which was not present on the spent catalyst S2, as shown in FIG. Figure 2 shown.

[0158] Catalyst R3 has 347m 2 / g, which accounts for 90% of the BET specific surface of the new catalyst A. It also has a pore volume of 0.58 ml / g, which accounts for 96% of the pore volume of the new catalyst A.

[0159] Example 6: Obtaining regenerated catalyst R4 (according to the present invention)

[0160] Another part of the spent catalyst S2 was regenerated at 400°C in an oxidizing atmosphere at a water-free air flow rate of 450 Sl / l / h for 2 hours. A regenerated catalyst R4 was obtained, which contained 0.56 wt. % carbon and 0.39 wt. % sulfur. Its metal components were unchanged compared to the new catalyst A. No NiMoO4 phase was detected by XRD analysis, as shown in FIG. Figure 2 shown.

[0161] Catalyst R4 has 370m 2 / g BET specific surface area and 0.58 ml / g pore volume, which account for 96% of the BET specific surface and 96% of the pore volume of the new catalyst A respectively.

[0162] Example 7: Catalytic Performance Quality of Catalysts A, S1, R1, R2, S2, R3 and R4

[0163] The performance qualities of the above catalysts were evaluated in the primary hydrocracking of a feedstock comprising a vacuum distillate fraction using an isothermal test pilot unit in a downflow configuration.

[0164] The test feedstock was previously hydrotreated. After the hydrotreatment stage, the test feedstock exhibited the properties shown in Table 1 below. In order to simulate the hydrogen sulfide and ammonia partial pressures generated in the hydrotreatment stage of the process, DMDS and aniline were added to the test feedstock, respectively, to obtain 15300 ppm by weight of sulfur and 1400 ppm by weight of nitrogen in the final added feedstock.

[0165] Characteristics of Hydrotreated Feedstocks

[0166] Table 1

[0167]

[0168]

[0169] Each catalyst was evaluated separately and sulfided using straight run gas oil with 4 wt% dimethyl disulfide (DMDS) and 2 wt% aniline added before hydrocracking tests. -1 , H2 / raw material volume ratio of 1000Sl / l, total pressure of 14MPa and temperature of 350°C for 6 hours.

[0170] After sulfidation, the operating conditions were adjusted to those used in the hydrocracking test: HSV was 1.5h -1 The H2 / feedstock volume ratio was 1000 Sl / l and the total pressure was 14 MPa. The temperature of the reactor was adjusted to achieve a target net conversion of 80% in the 375°C+ fraction after 150 hours under feedstock.

[0171] The performance qualities of the catalysts were compared with those of catalyst A, used as a reference, and are given in Table 2. The relative activity in degrees Celsius (°C) is obtained by the temperature difference required to achieve the same net conversion of 80% between catalyst A and the catalyst being evaluated. A positive value means that the catalyst being evaluated has a greater activity than catalyst A. HDN is the conversion of nitrogen present in the feed (applied at the same test temperature) without taking into account aniline, according to the following calculation:

[0172] %HDN = (ppmN_feedstock - ppmN_effluent) / (ppmN_feedstock)

[0173] The relative volume activity (RVA) was then calculated as follows (assuming that HDN is a first order reaction):

[0174] RVA_HDN=ln(1 / (1-%HDN_catalyst)) / ln(1 / (1-%HDN_catalyst_A))x100

[0175] The performance qualities of catalysts A (fresh), S1 and S2 (spent catalysts), R1, R2, R3 and R4 (regenerated catalysts) are compared. As described in Examples 1 to 6, the regeneration temperature, carbon content and possible presence of NiMoO4 phase are mentioned in the table.

[0176] Table 2

[0177]

[0178] The above observed catalytic performance qualities demonstrate the advantage of regenerating the catalyst at a lower temperature (in this case 400° C.) than the temperature usually applied according to the teaching obtained from the prior art (480° C. for the counter example provided). This is because, under the same HSV, pressure and inlet feed conditions, the target conversion activity is obtained at temperatures that are 4° C. and 5° C. lower, respectively, relative to the temperature of the comparative example.

[0179] Furthermore, at the same test temperature, it was also shown that the efficiency of the catalyst regenerated according to the invention (at 400° C.) increased, having 90-94% of the HDN activity of the fresh catalyst, whereas the catalyst regenerated at a higher temperature (480° C.) did not allow obtaining an efficiency better than 65-70% of the HDN activity of the fresh catalyst.

[0180] The regeneration method according to the invention is therefore attractive to refineries, which have the possibility to regenerate the catalyst with lower energy consumption (lower regeneration temperature) while obtaining a more efficient catalyst, even though the regenerated catalyst may contain residual coke (0.32% by weight or 0.56% by weight in this case in the examples according to the invention). Without being able to link these results to any one theory, the advantages of the invention may be related to obtaining a satisfactory specific surface and pore volume without generating excessive amounts of sulfidation-resistant crystalline phases, such as, for example, NiMoO4.

Claims

1. A process for regenerating an at least partially spent catalyst resulting from a hydrocracking process, said at least partially spent catalyst resulting from a fresh catalyst comprising at least one metal from group VIII, at least one metal from group VIB and a support comprising at least one zeolite, said process comprising at least one regeneration stage in which the at least partially spent catalyst is subjected to a heating and / or hydrothermal treatment at a temperature ranging from 350° C. to 460° C. in the presence of an oxygen-containing gas, so as to obtain a regenerated catalyst, said process not comprising a subsequent rehabilitation stage of contacting the regenerated catalyst with at least one organic or inorganic and acidic or basic compound.

2. A process as claimed in the preceding claims, wherein the content of metals from group VIII in the fresh catalyst is less than 20% by weight, preferably from 0.03% to 15% by weight, very preferably from 0.5% to 10% by weight and still more preferably from 1% to 8% by weight, expressed as oxides of metals from group VIII, relative to the total weight of the fresh catalyst, and the content of metals from group VIB in the fresh catalyst is from 1% to 50% by weight, preferably from 5% to 40% by weight and more preferably from 10% to 35% by weight, expressed as oxides of metals from group VIB, relative to the total weight of the fresh catalyst.

3. A process as claimed in any one of the preceding claims, wherein the zeolite is selected from zeolites belonging to the FAU, BEA, ISV, IWR, IWW, MEI, UWY, MEL, MTW, MTT, MRE, FER or MFI groups, and preferably the zeolite is selected from 10-MR or 12-MR zeolites, or preferably from the FAU or BEA groups.

4. A process as claimed in any one of the preceding claims, wherein the support of the fresh catalyst comprises USY zeolite and / or beta zeolite, alone or as a mixture, and preferably the support comprises USY zeolite.

5. A process as claimed in the preceding claims, wherein when the support comprises a USY zeolite, the latter has a lattice parameter of 24.10 to More preferably 24.15 to Still more preferably 24.20 to The Si / Al molar ratio is 2 to 300, more preferably 2.5 to 150, still more preferably 2.5 to 100, and the BET specific surface area is greater than 500 m 2 / g, more preferably 600 to 1100 m 2 / g, still more preferably 750 to 1000 m 2 / g, the mesopore volume is 0.05 to 0.9 ml / g, more preferably 0.08 to 0.7 ml / g, and still more preferably 0.1 to 0.6 ml / g.

6. A method as claimed in any of the preceding claims, wherein the oxygen content of the gas used in the regeneration phase is from 2% to 20% v / v, more preferably from 5% to 20% v / v, and still more preferably the gas used is air alone, the water content of the gas used in the regeneration phase is from 0 to 1000 g of water per kg of dry air, preferably from 0 to 500 g of water per kg of dry air, in a preferred manner from 0 to 250 g of water per kg of dry air, and still more preferably from 0 to 100 g of water per kg of dry air, and the duration of the regeneration phase is greater than 1 hour, more preferably from 1 to 100 hours, preferably from 1.5 to 25 hours, and particularly preferably from 2 to 10 hours.

7. A process as claimed in any one of the preceding claims, wherein the regeneration phase of the at least partially spent catalyst is carried out at a temperature of 360 to 450°C, preferably 370 to 430°C and still more preferably 380 to 420°C.

8. A process as claimed in any of the preceding claims, wherein the regenerated catalyst contains a residual carbon content of less than 2% by weight, preferably less than 1.5% by weight, particularly preferably less than 1% by weight and very preferably from 0.01% by weight to 0.8% by weight, relative to the total weight of the regenerated catalyst.

9. A process as claimed in any one of claims 1 to 7, wherein the regenerated catalyst contains no residual carbon.

10. A process as claimed in any one of the preceding claims, wherein the regenerated catalyst contains less than 3% by weight, preferably less than 2% by weight, in a preferred manner between 0.01% and 1.5% by weight and still more preferably between 0.1% and 1.2% by weight of residual sulfur, relative to the total weight of the regenerated catalyst.

11. Use of a catalyst obtained according to a process as claimed in any one of claims 1 to 10 in a process for the hydrocracking of hydrocarbon fractions.

Citation Information

Patent Citations

  • Catalyseur utilisable en hydrotraitement comprenant des metaux des groupes viii et vib et preparation avec de l'acide citrique et du succinate de dialkyle c1-c4

    FR2972648A1

  • Process for the rejuvenation of a spent molecular sieve catalyst

    US20130137913A1

  • Catalyst for use in hydrotreatment, comprising metals from groups viii and VIB, and preparation with citric acid and c1-c4 dialkyl succinate

    US20140076780A1

  • Process for rejuvenating hydrotreating catalyst

    US20170036202A1

  • Methods for regenerating and rejuvenating catalysts

    US20180318822A1